E-cigarettes, is this alternative safe? - Małgorzata Romaniuk; Konrad Suswał; Mateusz Komisarczuk; Weronika Tuszyńska; Karol Krupa; Wojciech Zygmunt; Janusz Milanowski (Kazimierz Wielki University, 2020)
Electronic cigarettes are often presented as a safer alternative to classic cigarettes. We present an overview of the latest data on the safety of using e-cigarettes and their impact on the respiratory and cardiovascular systems. The statement that e-cigarettes are much less harmful seems too hasty due to the relatively short presence of e-cigarettes on the market. We need more years of research on large groups of patients to help us answer the question whether e-cigarettes are a better and safer form of smoking.